The future of Catholicism in America - Killen, Patricia O'Connell; Silk, Mark (Future of religion in America., 2019)
This volume considers Catholicism's prospects at a pivotal moment. Contributors-scholars from sociology, theology, religious studies, and history-look at the church's evolving institutional structure, its increasing ethnic diversity, and its changing public presence